Pro PHP Security: From Application Security Principles to the Implementation of XSS Defenses, Second Edition - Snyder, Chris (Apress, 2012)
As far as organization goes, you’ll find that most of the information from the first edition is present in this book, but it’s been reordered so as to emphasize what web developers care about most: their own code, their own database queries, and their own code base. The book then expands to take into account safe operations (like using Captchas and safe execution of remote procedure calls) and then finishes up with creating a safe environment.